(untitled) (Politeja, 2025)
EU–AFRICA RELATIONS. BEYOND THE RHETORIC OF “THE PARTNERSHIP OF THE EQUAL” The article aims to verify the ‘partnership of equals’ narrative that the European Union uses in its relations with Africa. The article is written within the interpretivist epistemology. The main research techniques used during the work on the text were a critical analysis of the literature and a qualitative analysis of the official positions of the European Commission. The results obtained through these research techniques are compared with the results of field research conducted in the Southern African region. The text discusses the multidimensional inequalities in Euro-African relations, which have their roots in the colonial period when European integration began. The article points out that, as was the case in the ‘Treaties of Rome’, the language used by the European Commission concerning Africa today is characterised by paternalism. Africa remains a constitutive Other for the European Union, which allows the EU to define itself through the prism of what it is not and what it does not want to become.